A comparison of patient-reported quality between inpatient services for mental and physical health: A tertiary-hospital-based survey in China - Zhou, Wei; Xiao, Shuiyuan; Xie, Guanqing; Ouyang, Feiyun; Luo, Bihua (Frontiers in Psychiatry, 2023)
Background It is widely acknowledged that quality of mental health services is routinely worse than physical health services across countries. However, studies separately investigating mental health services often report high-level satisfaction, even comparing with physical health services. Therefore, this study aimed to compare patient-reported quality between inpatient services for mental and physical health in China. Methods An inpatient survey was conducted among service users of mental and physical health services. Patient-reported quality was measured by the responsiveness performance questionnaire after patient discharge and based on patients’ multiple experiences in the past three years. Chi-square tests were performed to compare the two patient groups’ ratings on mental and physical health services, and multivariate logistic regression was performed to adjust covariates in the group comparison. Results Mental health services were rated better than physical health services on “treating with respect” (AOR=3.083, 95% CI=1.102-8.629) and “choosing a healthcare provider” (AOR=2.441, 95% CI=1.263-4.717). However, mental health services had poorer ratings on “asking patient’s opinions” (AOR=0.485, 95% CI=0.259-0.910). For other responsiveness items, no significant difference was detected between the two types of services. Conclusions China’s mental health services, particularly at tertiary level, performed as well as physical health services in most aspects and even better performed regarding dignity and choice of healthcare providers. However, neglecting patients’ voices was more severe in mental health services.